Maternal Decision Support Systems to Reduce Maternal Mortality in Indonesia: Resolving Barriers to Implementation in Community Health Centers - Maryani Setyowati; Agung Wardoyo; Jaka Prasetya; Anastacia Rheinata Wibowo; Mufid Makantar (Green Publisher Indonesia, 2022)
Aim: This paper aims to design a decision support system in Maternal and Child Health services or MCH that can monitor cases of pregnant women and prevent maternal deaths because maternal deaths are still found in Semarang. Indonesia. Method = Research and Development with system development using the System Development Life Cycle method, which includes studying user needs, analyzing the system used, determining the form of the system being developed, and designing the Maternal Decision Support System. The sample of this research is in the form of MCH service data in 2019 - 2021. Meanwhile, respondent data collection is carried out by interviewing MCH Program Holders and observing the system used, analyzing MCH data, and designing a region-based Decision Support System using PHP programming and MySQL database. Result: The development of an MCH decision support system application that can support the area-based MCH program is https://spk-maternal.com/. It is easy to use by officers at the community health centers and the Health Office to monitor pregnancy history to reduce maternal mortality. Conclusion = Results of our study indicate that a district-based decision support system is easy to use to reduce maternal mortality. The study's findings indicate a need for tremendous support from the government to make policies based on a decision support system for appropriate maternal and child health services.